Iatrogenic peripheral nerve injury: a guide to management for the orthopaedic limb surgeon. Issue 8 (August 2021) - Bage, Timothy; Power, Dominic M.
Abstract : Nerves may be inadvertently injured during trauma surgery due to distorted anatomy, traction applied to a limb, soft tissue retraction, by power tools, instrumentation and from compartment syndrome. Elective orthopaedic surgery has additional risks of joint dislocation for arthroplasty surgery, limb lengthening, thermal injury from cement and direct injury from peripheral nerve blocks. The true incidence is unknown, and many cases are diagnosed as neurapraxia with the expectation of a full and timely recovery without the need for intervention. The incorrect assignation of a neurapraxia diagnosis may delay treatment for a higher grade of injury and in addition fails to recognize that a diagnosis of neurapraxia should be made with caution and a commitment to regular clinical review. Untreated, a neurapraxia can deteriorate and result in axonopathy. The failure to promptly diagnose such a nerve injury and instigate treatment may result in further deterioration and expose the clinician to medicolegal challenge. The focus of this review is to raise awareness of iatrogenic peripheral nerve injuries in orthopaedic limb surgery, the importance of regular clinical examination, the role of investigations, timing and nature of interventions and also to provide a guide to when onward referral to a specialist peripheral nerve injury unit is recommended. Cite this article: EFORT Open Rev 2021;6:607-617. DOI: 10.1302/2058-5241.6.200123